2009
DOI: 10.1002/ccd.22055
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical experience with the new amplatzer ductal occluder II for closure of the persistent arterial duct

Abstract: The ADO II is highly effective at providing rapid occlusion of morphologically varied PDAs. Occluder design allows closure with arterial or venous approach and delivery with 4 or 5 F delivery catheters. Stable occluder position is dependent on correct positioning of both aortic and pulmonary discs. A larger range of sizes and configurations of this occluder may be required to successfully occlude all ductal sizes and morphologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
71
0
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 18 publications
6
71
0
4
Order By: Relevance
“…We have demonstrated that percutaneous treatment with ADO2 can be realized with lower complication and residual shunt rates. The immediate and short term follow up success rate (complete occlusion) for duct occlusion by ADO2 at 24 hours, 7 days and 1 month was 97% respectively in our series which compares favourably with data reported using Amplazter ADO2 devices 7 . The multiple layers of nitinol allow for rapid ductal occlusion which reduces residual shunt risks.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…We have demonstrated that percutaneous treatment with ADO2 can be realized with lower complication and residual shunt rates. The immediate and short term follow up success rate (complete occlusion) for duct occlusion by ADO2 at 24 hours, 7 days and 1 month was 97% respectively in our series which compares favourably with data reported using Amplazter ADO2 devices 7 . The multiple layers of nitinol allow for rapid ductal occlusion which reduces residual shunt risks.…”
Section: Discussionsupporting
confidence: 89%
“…The multiple layers of nitinol allow for rapid ductal occlusion which reduces residual shunt risks. The ability to position the ADO2 such that each of the retention discs assumes its independent orientation significantly reduces the risk of protrusion, anatomical distortion and displacement which has resulted in a 97% (n=31) success rate of device deployment in our series with only one (3%) re-intervention due to device dislodgement which compares favourably with reported data 7 .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations